Antibody-Based Protective Immunity against Helminth Infections: Antibody Phage Display Derived Antibodies against BmR1 Antigen - Rahumatullah, Anizah; Abdul Karim, Izzati Zahidah; Noordin, Rahmah; Theam, Soon Lim (MDPI, 2017)
Helminth parasite infections are significantly impacting global health, with more than two billion infections worldwide with a high morbidity rate. The complex life cycle of the nematodes has made host immune response studies against these parasites extremely difficult. In this study, we utilized two phage antibody libraries; the immune and naïve library were used to identify single chain fragment variable (scFv) clones against a specific filarial antigen (BmR1). The V-gene analysis of isolated scFv clones will help shed light on preferential VDJ gene segment usage against the filarial BmR1 antigen in healthy and infected states. The immune library showed the usage of both lambda and kappa light chains. However, the naïve library showed preferential use of the lambda family with different amino acid distributions. The binding characteristics of the scFv clones identified from this work were analyzed by immunoassay and immunoaffinity pull down of BmR1. The work highlights the antibody gene usage pattern of a naïve and immune antibody library against the same antigen as well as the robust nature of the enriched antibodies for downstream applications.